Disrupting biological sensors of force promotes tissue regeneration in large organisms - Kellen Chen (Nature Portfolio, 2021)
Humans and other large mammals heal wounds by forming fibrotic scar tissue with diminished function. Here, the authors show that disrupting mechanotransduction through the focal adhesion kinase pathway in large animals accelerates healing, prevents fibrosis, and enhances skin regeneration.